CONTINUOUS IMPROVEMENT CYCLE-BASED EVALUATION: AN EFFECTIVE CONTROL STRATEGY FOR PROGRAMME SUCCESS - Busnawir Busnawir (Indonesian Journal of Education (INJOE), 2025)
This study aims to analyse the application of continuous improvement cycle-based evaluation and its integration with effective control strategies in order to increase the chances of programme success. The method used is a literature review with a descriptive-analytical approach, which examines concepts, theories, and empirical findings from various scientific sources such as journals, books, and research reports. The results of the study indicate that the application of a continuous improvement cycle model, such as Plan-Do-Check-Act (PDCA), enables program evaluation to be carried out systematically, adaptively, and repeatedly, so that weaknesses can be identified and corrected quickly. Meanwhile, effective control strategies—including the establishment of clear performance indicators, continuous monitoring, proactive risk management, strong governance, and the use of technology—can strengthen the evaluation process and ensure the efficient achievement of programme objectives. The synergy between these two approaches not only improves programme performance and quality but also fosters an organisational culture that is responsive, accountable, and quality-oriented. These findings have important implications for programme managers across sectors to adopt an integrated evaluation-control framework as a long-term management strategy.